Improving CMTS Physical Properties Through Potassium Doping for Enhanced Rhodamine B Degradation - Amira Bouali; Olfa Kamoun; Moez Hajji; Ileana Nicoleta Popescu; Ruxandra Vidu; Najoua Turki Kamoun (Technologies)
This study investigated the enhancement of Cu2MnSnS4 (CMTS) thin films’ photocatalytic properties through potassium (K) doping for rhodamine B degradation under visible light. K-doped CMTS films synthesized using spray pyrolysis technology achieved a 98% degradation efficiency within 120 min. The physical property improvements were quantitatively validated through X-ray diffraction (XRD) analysis, which confirmed enhanced crystallinity. Scanning electron microscopy (SEM) revealed significant modifications in surface morphology as a function of potassium content, highlighting its influence on film growth dynamics. Optical characterization demonstrated a pronounced reduction in transmittance, approaching negligible values at 7.5% potassium doping, and a narrowed optical band gap of 1.41 eV, suggesting superior light absorption capabilities. Photocatalytic performance was significantly enhanced, achieving a Rhodamine B degradation efficiency of up to 98% at 7.5% doping. These enhancements collectively improved the material’s light-harvesting capabilities and charge separation efficiency, positioning K-doped CMTS as a highly effective photocatalyst compared to other ternary and quaternary materials.